Pengelolaan dan Pengawasan Dana Desa Babakan Dayeuh, Cileungsi, Bogor - Latipah Nasution; Ahmad Tholabi Kharlie; Irfan Khairul Umam (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2019)
AbstractThis study aims to describe and analyze the management and utilization of village funds in Desa Dayeuh in terms of applicable laws and regulations. The aim is to find out what is the problem of ineffective village funds in Babakan Dayeuh Village. To achieve these objectives, researchers use legal research methods that are Normative and Empirical approaches. While the data collection techniques used in this study are field research and library research. Field research consists of observation, selection of information documents, and identification. Based on the results of this study indicate that the management and supervision of the Village Fund in Babakan Dayeuh Village has not been carried out according to applicable regulations, because village governments often ignore the rules that become a reference in managing Village funds such as; Regulation of the Minister of Disadvantaged Villages, Development and transmigration in the form of rules related to the Priority of Village Funds where the aim is that development in the village is directed according to the vision of the National Government.Keywords: Village Funds, Village Fund Management, Village Fund Supervision